Edukasi Pencegahan Pernikahan Dini pada Remaja di SMA N 7 Kota Jambi - Jayanti, Ova; Patriani, Sirly; Sinulingga, Selpyani (Universitas Baiturrahim, 2025)
Adolescence is a time when the development of reproductive organs begins. Adolescence is considered a sensitive period because there is a transition from childhood to adulthood which is filled with turmoil. At that time, adolescents will tend to search for their identity. Wrong associations and information will actually lead adolescents to high-risk sexual behavior habits and will ultimately lead them to early marriage. School is the right environment for adolescents to get information. Therefore, adolescents need to be given education about preventing early marriage. Educational activities were carried out at SMA N 7 Kota Jambi on February 24, 2024, which was attended by 22 female students. The time needed for educational activities is ± 60 minutes. The first 30 minutes of material presentation using ppt and leaflets were given to each participant. Furthermore, a discussion and question and answer session was carried out. After the education was completed, a posttest was carried out again, the level of adolescent knowledge was obtained from 82.58 to 93.42. It was concluded that there was an increase in adolescent knowledge about the impacts of early marriage, both physical, mental, economic and social impacts.